TRUE UMBILICAL CORD KNOT: CASE REPORT - García Agudelo, Lorena (2024)
ABSTRACTIntroduction. A true knot of the umbilical cord (TNUC) can lead to adverse perinatal outcomes, including hypoxia, lowApgar scores, small-for-gestational-age infants, and intrauterine fetal demise. TNUC occurs in 0.3% to 1.2% of pregnancies. Case presentation. A neonate was born to a 33-year-old multiparous woman in her fourth pregnancy, achievedthrough in vitro fertilization. The pregnancy was characterized by normal prenatal assessments and ultrasound findings.An emergency cesarean section was performed due to signs of fetal distress detected by fetal monitoring six hours afterthe onset of labor. A postnatal diagnosis of a true knot of the umbilical cord was made. The neonate had no abnormalities,congenital anomalies, or deviations in birth weight. Conclusion. The significance of true knot of the umbilical cord lies inthe necessity for careful prenatal monitoring, considering the potential for serious perinatal outcomes.